OPTIMASI PEMBUATAN BIOETANOL DARI NIRA KOLI ( Borassus flabeliefer Linn) MELALUI PROSES FERMENTASI - Letelay, Leonard Kristofel ; Malle, Dominggus; Nazudin, Nazudin (Program Studi Pendidikan Kimia, FKIP, Universitas Pattimura (Chemistry Education Study Program, Faculty of Teacher Training and Educational Sciences, Pattimura University), 2024)
This study was aims to optimize bioethanol production from Borassus palmyrah and to determine content of yield optimization bioethanol fermentation. Fermentation process conducted by Borassus palmyrah optimize found ammonium sulfate addition in fermentation bottled depth as nitrogen resources. Fermentation process done by 10 g of yeast, 15 g of yeast, and 20g of yeast. This bioethanol will be used as a renewable energy source that uses Borassus palmyrah as a raw material. Qualitative test was conducted by a graph method and HPLC method. The result of the research showed that ethanol content with the addition of ammonium sulfate based on the graphic method was 77% - 85%, and the results test using HPLC was obtained an ethanol content of 98.41% - 99.72%. Thus, it can be concluded that the optimal bioethanol production process is more efficient by adding ammonium sulfate and yeast as a biocatalyst. Keywords: bioethanol, Borassus. Sp, distillation, fermentation.